PENGARUH PERBEDAAN KONSENTRASI ACCUZUUR TERHADAP LAMA HANCUR JARUM SUNTIK DI PUSKESMAS GAJAHAN KOTA SURAKARTA - Margo Utomo; Munawaroh - (Universitas Muhammadiyah Semarang, 2008)
Background: Immunization and treatment in Gajahan Publio Health Centre yield clinic wasted, injection needlg yield mean 24 needles. Periodical in immunization at school yield clinic waste mean 5000 needles. It has potential to generate danger, environmental contamination if thrown by any place. Gajahan Public Health Centre not yet owned processing special unit and destruction of clinic waste because the limited farm. Accuuzuur is Acid Sulfate havs experienced of liquid with rate 38,065 %o. Mixture iron represent elementary materials of hypodermic needle, iron will be eroded at acid condition.Objective: Knowing influence difference of four kind concentration accuzuur to breaking duration time to hypodermic needles Method: A randomized post test only control group design, on 150 hypodermic needles, devise to 15 tubes, which has been filled 500 cc accuzuur with 85 o/o, 90o/o, 95 o/o and I 00 o/o concentration, and 500 cc aquadest for controlled group.Controled variable were type of needle, amount of needle, temperature, humidity and kind of tubes. The hypodermic needles being cut on covered with plastic. Treatment of final of accuzuur garbage, was given calcium carbonat little bits until pH 6,5-8,5, and then were been throwed . Statistic analyzed with One Way Anova.Result: From 100 ?'o concentration starting to break after 24 hours, and all needles breaked entirely after 72 hours. In 95 o/o concentration starting to break after 24 hours, and all needles breaked entirely after 96 hours. In 90% concentration starting to break after 48 hours, and all needles breaked entirely after 96 hours. In 85 o/o concentrationstarting to break after '12 hours. and all needles breaked entirely after 120 hours. There are no sigrificant difference among 85 % with 90%o,95 Yo, and there is significant difference among 85% with 100 %o concentration (p:0.004) at24 hours exposed. There are significant difference among four kind ofconcentration at 48 hours, 72 hours and 96 hours.Conclusion: 100 %o concentration is the most effective, and all needles were breaking after 120 hours.